Streothrips jianshuiensis sp. n., a tropical addition to the Aeolothripidae fauna of China (Thysanoptera) - Liu, Hui; Mound, Laurence; Zhang, Hongrui (Zootaxa, 2020)
Streothrips jianshuiensis sp.n. is described from Yunnan, China, as the fourth species in this genus from the Oriental tropics. A key is provided to the five genera of Aeolothripidae recorded from China.